2004
DOI: 10.1177/088307380401900506
|View full text |Cite
|
Sign up to set email alerts
|

Frontal and Caudate Alterations in Velocardiofacial Syndrome (Deletion at Chromosome 22q11.2)

Abstract: This study investigated the morphology of the frontal lobe and the caudate nucleus in velocardiofacial syndrome, a neurogenetic disorder caused by a microdeletion at chromosome 22q11.2 and frequently associated with severe psychiatric disturbances. Volumes of the caudate nucleus and subregions of the frontal lobe were compared on magnetic resonance images of 10 children with velocardiofacial syndrome and 10 age- and gender-matched controls. Frontal deep white matter was reduced significantly (by about 23%) in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
70
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 85 publications
(79 citation statements)
references
References 42 publications
8
70
0
Order By: Relevance
“…The 22q11.2 deletion mouse model displayed several differences that mirrored what has been found in human 22q11.2 deletion syndrome [139][140][141]. Specifically, the larger striatum, smaller cerebellum, and smaller amygdala in the mouse model are all consistently found in human patients.…”
Section: Recent Investigations (2010-14)mentioning
confidence: 66%
“…The 22q11.2 deletion mouse model displayed several differences that mirrored what has been found in human 22q11.2 deletion syndrome [139][140][141]. Specifically, the larger striatum, smaller cerebellum, and smaller amygdala in the mouse model are all consistently found in human patients.…”
Section: Recent Investigations (2010-14)mentioning
confidence: 66%
“…The observation of thicker cortex partially modifies the classical view that patients with 22q11DS consistently show differences in the reduced direction. Indeed, volumetric studies have always reported reduced cortical volume in the syndrome (Eliez et al, 2000;Kates et al, 2004Kates et al, , 2001Simon et al, 2005;van Amelsvoort et al, 2001). If cortical volume is undeniably the product of its surface and thickness, surface changes are more susceptible to result in volumetric changes than thickness alterations (Im et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…206 Imaging studies of caudate in adults with BD have been ambiguous, with some studies also showing an increased volume, 207 but other suggesting either a difference in the opposite direction-decreased caudate in older bipolar patients, particularly those with illness onset after 45 years of age 208 -or no differences in patients with minimal exposure to antipsychotics, 209 hospitalized manic patients, 210 bipolar patients, 211 or first-episode manic patients. 212 The heritability of caudate volume is unknown, but enlarged caudate volumes are associated with both genetic 213,214 and environmental factors, 215 including antipsychotic use. No association between antipsychotics or mood-stabilizing medications and caudate volume was reported in the above reviewed studies of BD, however.…”
Section: Basal Gangliamentioning
confidence: 99%